Uncovering the whole genome silencers of human cells via Ss-STARR-seq - Xiusheng Zhu; Lei Huang; Chao Wang; Guoli Li; Biao Deng; Dashuai Kong; Xiaoxiao Wang; Rongrong Chang; Yi Gu; Qiuhan Wen; Siyuan Kong; Yuwen Liu; et al. (Nature Communications)
Abstract Silencers, the yin to enhancers’ yang, play a pivotal role in fine-tuning gene expression throughout the genome. However, despite their recognized importance, comprehensive identification of these regulatory elements in the genome is still in its early stages. We developed a method called Ss-STARR-seq to directly determine the activity of silencers in the whole genome. In this study, we applied Ss-STARR-seq to human cell lines K562, LNCaP, and 293 T, and identified 134,171, 137,753, and 125,307 silencers on a genome-wide scale, respectively, these silencers function in various cells in a cell-specific manner. Silencers exhibited a substantial enrichment of transcriptional-inhibitory motifs, including REST, and demonstrated overlap with the binding sites of repressor transcription factors within the endogenous environment. Interestingly, H3K27me3 did not reflect silencer activity but facilitated the silencer’s inhibitory role on gene expression. Additionally, the silencer did not have any significant histone markers at the genome-wide level. Our findings unveil that aspect-silencers not only transition into enhancers throughout diverse cell lines but also achieve functional conversion with insulators. Regarding to biological effects, knockout experiments underscored the functional redundancy and specificity of silencers in regulating gene expression and cell proliferation. In summary, this study pioneers the elucidation of the genome-wide silencer landscape in human cells, delineates their global regulatory features, and identifies specific silencers influencing cancer cell proliferation.